Pelatihan Digital Merketing pada UMKM Rintisan di Sektor Industri Rumah Tangga - Albert Andhika Endratama; Ika Wulandari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The development of Micro, Small, and Medium Enterprises (MSMEs) is crucial to a country's economy. The growth of MSMEs in the realm of digital marketing has seen significant advancements alongside technological developments and changes in consumer behavior. Digital marketing can be a highly effective tool for increasing sales, expanding the market, and building long-term relationships with customers. Digital marketing allows MSMEs to reach a broader market, even beyond their local or national boundaries. However, applying digital marketing to newly established and home-based MSMEs can be challenging. Therefore, the author conducted basic digital marketing training for nascent MSMEs operating in the household sector. The goal of this training is to help MSME entrepreneurs understand the importance of digital marketing and to enable them to develop their businesses through digital marketing. Following this digital marketing training, the understanding of MSME entrepreneurs has been increased very well about digital marketing for the advancement of their businesses. Additionally, they have also tried promoting their products on social media platforms such as WhatsApp stories and Instagram stories.